2013
DOI: 10.1021/pr301217b
|View full text |Cite
|
Sign up to set email alerts
|

Glycoproteomic Discovery of Serological Biomarker Candidates for HCV/HBV Infection-Associated Liver Fibrosis and Hepatocellular Carcinoma

Abstract: We previously proposed a high-throughput strategy to discover serological biomarker candidates of cancer. This strategy focuses on a series of candidate glycoproteins that are specifically expressed in the original tissues (cells) of the target cancer and that carry glycan structures associated with carcinogenesis [Narimatsu, H., et al. FEBS J.2010, 277(1), 95-105]. Here, we examined the effectiveness of our strategy in identifying biomarkers to assess progression of liver fibrosis and for the early detection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 48 publications
2
50
0
Order By: Relevance
“…However, owing to the recent progress made in mass spectrometry (MS) equipment and other technologies, omics-based research has been actively pursued [29][30][31][32]. The major innovation in disease biomarker development is the high-throughput and comprehensive identification of glycobiomarker candidates and the strategic development of clinically useful biomarkers based on the newest MS technology as well as other leading technologies.…”
Section: Basic Concept Of Disease Glyco-biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…However, owing to the recent progress made in mass spectrometry (MS) equipment and other technologies, omics-based research has been actively pursued [29][30][31][32]. The major innovation in disease biomarker development is the high-throughput and comprehensive identification of glycobiomarker candidates and the strategic development of clinically useful biomarkers based on the newest MS technology as well as other leading technologies.…”
Section: Basic Concept Of Disease Glyco-biomarkersmentioning
confidence: 99%
“…Although it cannot identify site-specific glycan structures on a native protein and there is possibility of false-positive detection, the usefulness in prediction of potential biomarker candidates in a high-throughput manner outweighs the disadvantages. In the discovery of the fibrosis marker, the WFA-reactive glycopeptides were comprehensively captured, which resulted in identification of several hundreds of glycoproteins in serum from patients with liver fibrosis as potential biomarker candidates [32].…”
Section: As Listed Inmentioning
confidence: 99%
“…This strong binding enables direct and highly sensitive detection of a serum marker without the need of sample pretreatment for the purification of the target glycoprotein. Therefore, we selected glycoproteins containing many glycans for further development based on the bioinformatics analyses [6,7]. The candidates with more glycans are given higher priority.…”
Section: Selection Of Clinically Useful Glycoproteins From the Sea Ofmentioning
confidence: 99%
“…The remaining several hundreds of glycoproteins were ranked by bioinformatics analyses. The candidate proteins for which commercial antibodies were available were analyzed by western blotting and immunoprecipitation [6].…”
Section: Selection Of Clinically Useful Glycoproteins From the Sea Ofmentioning
confidence: 99%
“…Serum glycomic studies to discover novel glycan cancer biomarkers have been highlighted (Adamczyk et al 2012 ). Numerous glycan tumor marker candidates for various cancers, including liver (Kaji et al 2013 ;Kamiyama et al 2013 ;Wu et al 2012 ;Tang et al 2010 ;Goldman et al 2009 ;Comunale et al 2009 ;Tanabe et al 2008 ;Ressom et al 2008 ), ovary (Biskup et al 2013 ;Hua et al 2013 ;Alley et al 2012 ;Abbott et al 2010 ;Leiserowitz et al 2008 ), pancreas (Li et al 2009 ;Okuyama et al 2006), breast (de Leoz et al 2011Alley et al 2010 ;Zeng et al 2010 ;Storr et al 2008 ;Abd Hamid et al 2008 ;Kyselova et al 2008 ;Kirmiz et al 2007 ), prostate , lung (Arnold et al 2011 ), colorectum (Zhao et al 2012 ), bile duct (Silsirivanit et al 2011 ), and esophagus ) cancers, have been reported. Most of these glycomic analyses have been carried out by newly developed high-throughput platform technologies, such as mass spectrometry-based methods and lectin-based methods, which have enabled the effi cient analysis of large cohorts of samples.…”
Section: Glycomic Studies On Serum Of Cancer Patientsmentioning
confidence: 99%